The North Atlantic Alliance – Past, Present and Future (Czech Journal of International Relations, 2000)
Todd Sandler – Keith Hartley: The Political Economy of NATO. Past, Present, and into the 21st Ceutury. 1st ed. Cambridge: University Press, 1999, 292 stran, ISBN 0-521-63880-1 (paperback), ISBN 0-521-63093-2 (hardback).